2011
DOI: 10.1007/s12011-011-9121-y
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Exogenous Glutathione in Ultrastructure and Photosynthetic Performance Against Cd Stress in the Two Barley Genotypes Differing in Cd Tolerance

Abstract: Greenhouse hydroponic experiments were conducted using Cd-sensitive (Dong 17) and tolerant (Weisuobuzhi) barley genotypes to evaluate genotypic differences in response of photosynthesis and ultrastructure to Cd toxicity in the presence of exogenous glutathione (GSH). Addition of 20 mg L(-1) GSH in 5 μM Cd culture medium (Cd + GSH) significantly alleviated Cd-induced growth inhibition and reduced Cd concentration in leaves and roots especially in the sensitive genotype Dong 17. Exogenous GSH greatly ameliorated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(42 citation statements)
references
References 30 publications
(31 reference statements)
4
35
1
Order By: Relevance
“…In the present experiment, considerable increased Fo and reduced Fv/Fm were observed in cucumber under Cd stress. Similar results were observed in rice, soybean, tobacco and barley (Kao et al, 2003;Cai et al, 2011;Wang et al, 2011;Liu et al, 2015), however, there was no significant different in Y(NO) under Cd stress in comparison with control (Fig. 4).…”
Section: Se Balances Cd-induced Changes In Carbohydrate Contentssupporting
confidence: 83%
“…In the present experiment, considerable increased Fo and reduced Fv/Fm were observed in cucumber under Cd stress. Similar results were observed in rice, soybean, tobacco and barley (Kao et al, 2003;Cai et al, 2011;Wang et al, 2011;Liu et al, 2015), however, there was no significant different in Y(NO) under Cd stress in comparison with control (Fig. 4).…”
Section: Se Balances Cd-induced Changes In Carbohydrate Contentssupporting
confidence: 83%
“…Exogenous GSH resulted in the increase of plant dry weight in the following two barley varieties: Weisuobuzhi (by 42.3%) and Dong 17 (by 70.6%). The reduced shoot/root Cd concentrations of 33.8/42.2% in Weisuobuzhi and 59.4/66.3% in Dong 17 relative to the Cd alone treatment reflects that GSH can suppress plant Cd uptake (Wang et al 2011). …”
Section: Toxic Metals/metalloidsmentioning
confidence: 99%
“…Bergmann and Rennenberg (1993) also demonstrated a time-dependent increase in GSHS activity in same species upon exposure to Cd. Wang et al (2011) reported some injury symptoms, such as leaf chlorosis, necrosis and stunting in barley seedlings when subjected to Cd (5 lM). However, the addition of GSH (20 mg L -1 ) in the Cd culture medium can alleviate the Cd-induced growth inhibition and leaf injury symptoms significantly.…”
Section: Toxic Metals/metalloidsmentioning
confidence: 99%
See 2 more Smart Citations